Intramolecular Alkene Hydroamination with Hybrid Catalysts Consisting of a Metal Salt and a Neutral Organic Base. Issue 35 (2nd September 2020) - Stegner, Philipp C.; Fischer, Christian A.; Nguyen, D. Thao; Rösch, Andreas; Penafiel, Johanne; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd
Abstract : Hybrid catalysts consisting of alkaline earth iodides (AeI2 ) and the Schwesinger base t Bu P4 catalyse the intramolecular alkene hydroamination of H2 C=CHCH2 CR2 CH2 NH2 [CR2 =CPh2, C(CH2 )5, CMe2 ]. Activities decrease along the row: Ca > Sr >> Mg > Ba. Hybrid catalysts consisting of t Bu P4 and ZnI2, AlI3, FeCI3 or NaI were found to be fully inactive. Also, the hybrid catalyst t Bu P3/CaI2 was not active which means that the base strength of the non‐nucleophilic organic base must be higher than that of t Bu P3 (p K a BH + = 38.6). Combinations of t Bu P4 with CaX2 (X = Cl, Br, O i Pr, OTf, NTf2 ) were found to be fully inactive which may in part be explained by poor solubility. The hybrid catalysis method is therefore limited to the combination t Bu P4/CaI2 but the iodide ligands may be partially or fully replaced by chiral ligands. Chiral modifications of the hybrid catalysts gave in intramolecular alkene hydroamination ee values up to 33 %. Abstract : Influences of metal, ligand, and organic base in hybrid catalysts on intramolecular alkene hydroamination have been investigated.